The role of physical education in higher education in promoting and maintaining students’ mental health development - Wang, Xiaoyun; Zhao, Huiying; Ren, Tingting (Transactions on Social Science, Education and Humanities Research, 2024)
The purpose of this paper is to explore the role of physical education in colleges and universities in promoting and maintaining the development of students’ mental health. In the paper, we explain the importance of physical education to students’ mental health, and through analysing the current situation and problems of physical education in colleges and universities, we discuss the specific role and measures of physical education in colleges and universities in promoting and maintaining students’ mental health, including strengthening education and training, improving teaching quality, creating a positive and healthy learning environment, and the role of teachers, students, parents and other parties in promoting physical education and mental health in colleges and universities The responsibilities and roles of teachers, students and parents in promoting the development of physical education and mental health in colleges and universities. Finally, we conclude the importance of physical education in colleges and universities for students’ mental health, and offer some outlook and suggestions.